2017
DOI: 10.1111/jmg.12244
|View full text |Cite
|
Sign up to set email alerts
|

Microdiamond on Åreskutan confirms regional UHP metamorphism in the Seve Nappe Complex of the Scandinavian Caledonides

Abstract: Metamorphic diamond in crustal rocks provides important information on the deep subduction of continental crust. Here, we present a new occurrence of diamond within the Seve Nappe Complex (SNC) of the Scandinavian Caledonides, on Åreskutan in Jämtland County, Sweden. Microdiamond is found in situ as single and composite (diamond+carbonate) inclusions within garnet, in kyanite‐bearing paragneisses. The rocks preserve the primary peak pressure assemblage of Ca,Mg‐rich garnet+phengite+kyanite+rutile, with polycry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 99 publications
0
57
0
1
Order By: Relevance
“…Klonowska et al . [], for example, showed that in the Seve Nappe of the Scandinavian Caledonides both strong eclogites and peridotites and the surrounding weak gneissic matrix yield evidence for ultrahigh‐pressure conditions. According to the previously mentioned numerical models, on the other hand, this rheology contrast should have led to enormous tectonic overpressure and/or underpressure, which have not been detected.…”
Section: Discussionmentioning
confidence: 99%
“…Klonowska et al . [], for example, showed that in the Seve Nappe of the Scandinavian Caledonides both strong eclogites and peridotites and the surrounding weak gneissic matrix yield evidence for ultrahigh‐pressure conditions. According to the previously mentioned numerical models, on the other hand, this rheology contrast should have led to enormous tectonic overpressure and/or underpressure, which have not been detected.…”
Section: Discussionmentioning
confidence: 99%
“…Albrecht, ; Kullerud, Stephens, & Zachrisson, ; Nicholson, ; Santallier, ; Stephens & van Roermund, ) it was only recently discovered that the SNC experienced UHP metamorphism. The latter was documented in eclogites and ultramafic rocks of northern Jämtland (Brueckner, van Roermund, & Pearson, ; Gilio, Clos, & van Romermund, ; Janák, van Roermund, Majka, & Gee, ; Klonowska et al., ; Majka, Janák, et al., ) and in metasedimentary rocks of west‐central Jämtland (Klonowska, Majka, Janák, Gee, & Ladenberger, ; Klonowska et al., ; Majka, Rosén, et al., ). UHP metamorphism was constrained in west‐central Jämtland to >445 Ma via Th–U–Pb monazite geochronology (Klonowska et al., ; Majka et al., ).…”
Section: Geological Settingmentioning
confidence: 99%
“…A prominent core-rim texture such as that observed in the present case study could be attributed to a 614 multi-stage garnet growth, such as in the examples described by Konrad-Schmolke et al (2008) or 615 Klonowska et al (2017) in which two growth events occur at markedly different P-T conditions. 616…”
Section: Causes Of Inclusion-rich Vs -Poor Domains In Minerals 608mentioning
confidence: 52%
“…are not evidence of polymetamorphism (Konrad-Schmolke et al 2008), even though the P-T conditions 96 at which the two stages occur are markedly different (c. 3 GPa difference in Klonowska et al 2017). 97…”
Section: Introductionmentioning
confidence: 99%